2006
DOI: 10.2319/111105-395
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Size and Shape in 6-Year Olds Affected by Hypohidrotic Ectodermal Dysplasia

Abstract: Palatal size and shape were significantly modified by the presence of hypohidrotic ectodermal dysplasia, and the major alterations were found in edentulous HED subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…The mechanisms responsible for these subtle morphological changes remain unclear. Our results have to be supported by further investigations in order to precise whether these changes correspond to compensations for other craniofacial dysmorphologies – e.g., the reduced and retrognatic maxilla – observed in XLHED patients (Bondarets et al, 2002; Johnson et al, 2002; Dellavia et al, 2006) but not yet demonstrated in mutant Ta mice or are caused directly by the mutation itself. However, the noticeable mandibular changes parallel the marked abnormalities of the lower tooth row (Kristenova et al, 2002; Peterkova et al, 2002).…”
Section: Discussionmentioning
confidence: 54%
“…The mechanisms responsible for these subtle morphological changes remain unclear. Our results have to be supported by further investigations in order to precise whether these changes correspond to compensations for other craniofacial dysmorphologies – e.g., the reduced and retrognatic maxilla – observed in XLHED patients (Bondarets et al, 2002; Johnson et al, 2002; Dellavia et al, 2006) but not yet demonstrated in mutant Ta mice or are caused directly by the mutation itself. However, the noticeable mandibular changes parallel the marked abnormalities of the lower tooth row (Kristenova et al, 2002; Peterkova et al, 2002).…”
Section: Discussionmentioning
confidence: 54%
“…D ellavia et al. (11) found reduced palatal dimensions in boys with HED, which were significantly modified by the presence of teeth. The vertical dimension of hard tissue palate was smaller in completely edentulous than in partially dentate children.…”
Section: Discussionmentioning
confidence: 99%
“…To maximize the clinical therapeutic outcome in patients still undergoing skeletal growth, potential ED‐specific facial growth patterns should be assessed by using qualitative and quantitative methods (6). To date, facial features in ED‐affected subjects have been analyzed in several cephalometric and anthropometric investigations (1, 3–5, 11, 12). Recently, L exner et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] The scalp hair in patients with ED is often lightpigmented, thin, dry, brittle, and sparse; eyebrows and/or eyelashes may be sparse or absent. [6][7][8][9][10] Described hair disorders include the partial or total hair loss, chronic dermatitis of the scalp with the formation of crusts (Rapp-Hodgkin syndrome), trichorrhexis nodosa, pili torti, pili canaliculi, or trichothiodystrophy. [11][12][13][14][15][16] In recent years, physicians have utilized an additional diagnostic tool for hair and scalp disorders-trichoscopy (hair and scalp dermoscopy), 17-21 a rapid in-office technique, which has become a standard procedure in differential diagnosis of hair loss.…”
mentioning
confidence: 99%